Control of Flexible Joint Manipulator via Reduced Rule-Based Fuzzy Control with Experimental Validation. (3rd January 2012) - Rostami Kandroodi, Mojtaba; Mansouri, Mohammad; Aliyari Shoorehdeli, Mahdi; Teshnehlab, Mohammad
Abstract : A novel structure of fuzzy logic controller is presented for trajectory tracking and vibration control of a flexible joint manipulator. The rule base of fuzzy controller is divided into two sections. Each section includes two variables. The variables of first section are the error of tip angular position and the error of deflection angle, while the variables of second section are derivatives of mentioned errors. Using these structures, it would be possible to reduce the number of rules. Advantages of proposed fuzzy logic are low computational complexity, high interpretability of rules, and convenience in fuzzy controller. Implementing of the fuzzy logic controller on Quanser flexible joint reveals efficiency of proposed controller. To show the efficiency of this method, the results are compared with LQR method. In this paper, experimental validation of proposed method is presented.